Multiculturalism Education as the Social Approach for Deradicalization Program in Indonesia - Yumitro, Gonda; Abhiyoga, Nurdiana (Technium Social Sciences Journal, 2022)
This research examines multicultural education as a social strategy for deradicalization programs. This study aims to determine whether social approaches are beneficial for expanding deradicalization initiatives in Indonesia. Multicultural education is a social strategy that stems from the family, the surrounding environment, and the community, which can develop religious tolerance and cultural variety. Consequently, it can lessen conflicts that can escalate to violence and terrorism. Therefore, multicultural education is anticipated to create an attitude of tolerance, mutual understanding, and openness, in addition to all attitudes and values essential for social harmony and peace. In addition, According to this research, Islam is a religion of universal compassion (rahmatan lil 'alamin) that promotes education by protecting human values, bolstering human rights, valuing cultural diversity, and wishing for justice, peace, and a fair-minded perspective. This investigation was examined utilizing a qualitative methodology. Mendeley will perform an in-depth analysis and visualization of the data that the author discovered through the Scopus search engine, Publish or Perish.